PENGGUNAAN MEDIA BONEKA TANGAN DALAM PENERAPAN HAFALAN HADITS - Nurazizah, Indah; Suprihatin, Suprihatin; Tirtajaya, Mas Deden; Wastoni, Oni (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
Islamic religious education is an effort and method designed to help educators and students consistently understand correct moral knowledge. Apart from the scientific aspect, Islamic religious education is also considered a guide to human life. The results of problem analysis through observations and interviews regarding community service activities in Ridomanah Village, found that there was no teaching about Hadith. The community service program in this activity is about implementing Hadith memorization for TPQ children in Ridomanah Village with learning media in the form of hand puppets using a short story line method entitled "Don't Be Angry" which contains the Hadith saying good, the Hadith don't be angry, the Hadith the virtue of smiling. The aim of this research is to teach children about the importance of memorizing the Prophet's hadith, and develop their imagination through the use of hand puppets. The results of this community service activity are (1) Sharpening children's imagination from listening to short stories using hand puppets, (2) Increasing children's confidence in practicing stories using hand puppets, (3) Can increase knowledge about daily Hadith, and can memorize daily Hadith.